Laying the foundation for a primary care core set of the international classification of functioning, disability and health (icf) for community-dwelling older adults: A qualitative study - Tomandl, Johanna; Book, Stephanie; Höfle, Anina; Grässel, Elmar; Sieber, Cornel; Freiberger, Ellen; Kühlein, Thomas; Hueber, Susann; Gotthardt, Susann (Journal of Rehabilitation Medicine, 2021)
Objective: To explore relevant areas of functioning from the perspective of community-dwelling adults aged 75 years and over, in order to develop a Core Set of the International Classification of Functioning, Disability and Health (ICF) for community-dwelling older adults for use in primary care. Design: Qualitative study using semi-structured interviews and focus groups. Participants: A total of 27 community-dwelling older adults participated in the interviews and 24 of them in the focus groups. Methods: Following the proposed methodology of the ICF Research Branch, this is 1 of 4 preparatory studies in the Core Set development process. Within the transcripts, concepts of functioning were identified, based on Mayring s qualitative content analysis using deductive category assignment with the ICF being the category system. Results: Overall 6,667 concepts were identified. Most were linked to the Activities and Participation component. The most frequently identified categories were "recreation and leisure" and "family relationships". Conclusion: Categories from all ICF chapters were identified, demonstrating the complexity and multidimensionality of the ageing process, with a special emphasis on the component Activities and Participation. This qualitative study provides a list of relevant categories from the perspective of community-dwelling elderly people, which will be used to develop a Core Set for older primary care patients.
CRIS-Team Scopus Importer:2021-03-26
Keywords: aged; cross-sectional study; Disability and Health; focus group; general practice/methods.; geriatric assessment/ methods; independent living; International Classification of Functioning; interviews as topic